Kajian Kinerja Keuangan Daerah di Kabupaten Jembrana - I Gede Agus Wibawa; I Wayan Sudemen; Made Yaya Sawitri (Universitas Warmadewa, 2021)
Regional financial performance is the government from a work in the region that receives regional revenues and expenditures using a financial system determined through policies or statutory provisions for one budget period. Good management of the regional financial system must comply with the applicable provisions, management must be carried out with the principles of transparency, accountability, effectiveness and efficiency as well as targets and benefits. This study conducted an assessment of the 2019 level of mandatory Local Government Financial Reports (LKPD) from 2015 to 2015 to find the findings of the LKPD. This study aims to analyze problems related to the fulfillment of an Unqualified Opinion (WTP) by the examiner/auditor. Findings The results show that the real condition of the LKPD still needs to be improved, should the BPK RI Representatives of Bali Province give a maximum opinion on the Fair with Exception Criteria (WDP), very few relevant relevant opinions are given. The results of the measurement of regional financial management are expected to spur and motivate local governments in improving regional financial management performance, including the Jembrana Regency Government.